2007
DOI: 10.1111/j.1399-0004.2007.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation and phenotypic spectrum in patients with cardio‐facio‐cutaneous and Costello syndrome

Abstract: Cardio-facio-cutaneous (CFC) and Costello syndrome (CS) are congenital disorders with a significant clinical overlap. The recent discovery of heterozygous mutations in genes encoding components of the RAS-RAF-MAPK pathway in both CFC and CS suggested a similar underlying pathogenesis of these two disorders. While CFC is heterogeneous with mutations in BRAF, MAP2K1, MAP2K2 and KRAS, HRAS alterations are almost exclusively associated with CS. We carried out a comprehensive mutation analysis in 51 CFC-affected pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
95
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 31 publications
9
95
0
3
Order By: Relevance
“…Consistent with the available records, 2 -4,16 -18,20 -22 these data indicate that MEK1 and MEK2 gene mutations 4 Niihori et al, 2 Nava et al, 16 Narumi et al, 3 Yoon et al, 20 Armour et al, 22 Gripp et al, 21 Schulz et al, 17 As facial dysmorphisms are not reported among Armour and Allanson's cohort, we compared the MEK-mutated CFCS cohort with our unpublished clinical data of 17 CFC BRAF-mutated positive patients. MEK1 and MEK2 mutations in CFC syndrome ML Dentici et al underlie a significant fraction of CFCS, accounting for approximately 20% of cases.…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with the available records, 2 -4,16 -18,20 -22 these data indicate that MEK1 and MEK2 gene mutations 4 Niihori et al, 2 Nava et al, 16 Narumi et al, 3 Yoon et al, 20 Armour et al, 22 Gripp et al, 21 Schulz et al, 17 As facial dysmorphisms are not reported among Armour and Allanson's cohort, we compared the MEK-mutated CFCS cohort with our unpublished clinical data of 17 CFC BRAF-mutated positive patients. MEK1 and MEK2 mutations in CFC syndrome ML Dentici et al underlie a significant fraction of CFCS, accounting for approximately 20% of cases.…”
Section: Discussionsupporting
confidence: 76%
“…The number of fatal cases was 5/138 patients with p.G12S, 4/6 with p.G12C, 3/17 with p.G12A, 3/4 with p.G12D, 2/2 with p.G12V, 1/1 with p.G12E and 1/1 with p.E63K. 3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The mortality of patients with p.G12C or p.G12D was significantly higher than that of the patients with the more common p.G12S (P¼0.026 by Fisher's exact test). Previous studies have shown that the p.G12V substitution has the highest transformative potential (p.G12V4p.G12A, p.G12S, p.G12C, p.G12D4p.G13D) and is the most frequently found mutation in human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…3 It has been suggested that the CS diagnosis should be applied only to patients with a mutation in HRAS because of the high risk of malignancies associated with HRAS mutations and the relative homogeneity of the CS phenotype. 4 A total of 14 HRAS missense mutations and one duplication mutation have been reported in 185 patients with CS 3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] or congenital myopathy with excess of muscle spindles. 24 Most of these mutations have previously been reported as somatic and oncogenic mutations in various tumors.…”
Section: Introductionmentioning
confidence: 99%
“…We synthesized mRNA for WT MEK1; 14 reported RASopathy MEK1 variants (11)(12)(13)(14)(15)(16)(17)(18), of which 5 are also found in cancer (37); and two MEK1 variants that are found in cancer alone (37) (Fig. 1A and SI Appendix, Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, multiple new mutations were identified in MEK1, a MAPK kinase (10) and an important target for anticancer therapeutics (11)(12)(13)(14)(15)(16)(17)(18)(19). Because it is commonly believed that cancer mutations would be embryonic lethal when inherited through the germ line, it might be expected that mutations that cause developmental disorders, but allow survival of the carrier, are weaker than those that cause cancer (20).…”
mentioning
confidence: 99%